-4+8v=(v-4)-3v

Simple and best practice solution for -4+8v=(v-4)-3v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4+8v=(v-4)-3v equation:



-4+8v=(v-4)-3v
We move all terms to the left:
-4+8v-((v-4)-3v)=0
We calculate terms in parentheses: -((v-4)-3v), so:
(v-4)-3v
We add all the numbers together, and all the variables
-3v+(v-4)
We get rid of parentheses
-3v+v-4
We add all the numbers together, and all the variables
-2v-4
Back to the equation:
-(-2v-4)
We get rid of parentheses
8v+2v+4-4=0
We add all the numbers together, and all the variables
10v=0
v=0/10
v=0

See similar equations:

| 1/3(x-7)=1/3x+3 | | 2(h+8.3)-7.94=-1.34 | | 6y=480 | | 5x+15x=20+10 | | 6y+8=6(y+3)−10 | | N=1.2x+0.5 | | 12(5x+27)=4x-(6-9x) | | F(4)=3-2x | | x3+12=228 | | 347=-3+7(1-7x) | | 7(2m-3)=24 | | -8=-5y+12 | | 9=4y+15-3y | | 7x+4-9x=24 | | -2x-2=2(-x+1) | | 2(j+4)=12 | | 4(x+3)-x=3 | | -3(u+-2)=0 | | 5=2x+7-4x | | -2x+3-x=-9 | | 2x+7+x+61+x=80 | | }3x+9=51 | | (x/14)=7 | | 13=-8+21y-20y | | 24+x=35 | | 9x-8x-2=12 | | 6-7x=10x+9 | | 9x+65=180 | | 4z-5-10z=1 | | -7x+9x-4=6 | | 44=-9y+3y+2 | | x-3+x=13+6x |

Equations solver categories